2017
DOI: 10.4049/jimmunol.1601776
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Retinoid AM80 Ameliorates Lung and Arthritic Autoimmune Responses by Inhibiting T Follicular Helper and Th17 Cell Responses

Abstract: Rheumatoid arthritis (RA) is an autoimmune disorder that affects both joints and other organs. Pulmonary complications contribute significantly to RA mortality. Retinoic acid and its synthetic compound AM80 play roles in immunoregulation but their effect on mucosal autoimmunity remains largely unknown. T follicular helper (Tfh) and T helper 17 (Th17) cells are known to promote inflammation and auto-antibody (auto-Ab) production. Using the K/BxN autoimmune arthritis model, we elucidate a novel mechanism whereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Inducible bronchus-associated lymphoid tissue (iBALT) is a type of ectopic lymphoid tissue found in the lungs of patients with RA and is positively correlated with the severity of the patient’s lung disease [ 28 ]. Previously we have demonstrated that SFB colonization provoked young K/BxN mice to develop iBALT-like structures closely resembling the iBALT formations in patients with RA [ 29 , 30 ]. Here, we compared iBALT lesions between young and middle-aged groups with or without SFB colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Inducible bronchus-associated lymphoid tissue (iBALT) is a type of ectopic lymphoid tissue found in the lungs of patients with RA and is positively correlated with the severity of the patient’s lung disease [ 28 ]. Previously we have demonstrated that SFB colonization provoked young K/BxN mice to develop iBALT-like structures closely resembling the iBALT formations in patients with RA [ 29 , 30 ]. Here, we compared iBALT lesions between young and middle-aged groups with or without SFB colonization.…”
Section: Resultsmentioning
confidence: 99%
“…The inducible bronchus-associated lymphoid tissues (iBALT), a type of ELT found in the lung of RA patients, has been shown to correlate with lung tissue damage (Rangel-Moreno et al, 2006). K/BxN mice develop iBALT-like structures characterized by peribronchial and perivascular lymphocytic infiltration (Naskar et al, 2017). Thus, iBALT-like structures provide a clinically relevant index for RA-related lung disease in K/BxN mice.…”
Section: Introductionmentioning
confidence: 99%
“…Lung single cell preparation was described previously (Naskar et al, 2017 ). Briefly, lungs were perfused through the right ventricle of the heart with 10 ml of PBS to flush blood, then finely minced.…”
Section: Methodsmentioning
confidence: 99%